Pengaruh Corporate Social Responsibility Terhadap Kinerja Keuangan Perusahaan di Indonesia dengan Intellectual Capital dan Competitive Advantage Sebagai Variabel Mediasi - Parluhutan, Hehe Alfredo; Kesumo Wardhani, Nurhastuty (Economic Reviews Journal, 2026)
This research aims to examine and analyze the relationship between Corporate Social Responsibility and Financial Performance, with Intellectual Capital and Competitive Advantage as mediating variables. This research was conducted using secondary data obtained from the companies' annual reports. The sampling method in this research used a purposive sampling method. The samples used in this research are companies listed on the Indonesia Stock Exchange during a specific observation period. The data analysis method used to test the hypothesis is path analysis processed with statistical software. The results of the hypothesis testing in this research indicate that (1) Corporate Social Responsibility has a positive and significant effect on Intellectual Capital, (2) Corporate Social Responsibility has a positive and significant effect on Competitive Advantage, (3) Intellectual Capital and Competitive Advantage significantly mediate the relationship between social activities and financial achievement, and (4) integrated social practices are able to create long-term economic value for business entities.